Public Spending on Education in the Canadian Provinces: Some Comments on Ellis’ Paper Toward Reframing Rather than Recycling Old Ideas About Educational Expenditures - Hunter, Darryl M. (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
This short article provides a critique of Dr. Ellis’ paper in a recent edition of the Canadian Journal of Educational Administration and Policy (CJEAP), focusing on where future Canadian research in educational finance can have practical implications rather than simply offering transitory displays of polemical fireworks.